On the value of liquid-air and pumped-thermal electricity storage systems in low-carbon electricity systems. (15th February 2020) - Georgiou, Solomos; Aunedi, Marko; Strbac, Goran; Markides, Christos N.
Abstract: We consider two medium-to-large scale thermomechanical electricity storage technologies currently under development, namely 'Liquid-Air Energy Storage' (LAES) and 'Pumped-Thermal Electricity Storage' (PTES). Consistent thermodynamic models and costing methods based on a unified methodology for the two systems from previous work are presented and used with the objective of integrating the characteristics of the technologies into a whole-electricity system assessment model and assessing their system-level value in various scenarios for system decarbonization. It is found that the value of storage depends on the cumulative installed capacity of storage in the system, with storage technologies providing greater marginal benefits at low penetrations. Two carbon target scenarios showed similar results, with a positive effect of more ambitious carbon targets on the system value of storage. The location and installed capacity of storage plants is found to have a significant impact on the system value and acceptable costs of both technologies. The system value of PTES was found to be slightly higher than that of LAES, driven by a higher storage duration and efficiency, although these results must be seen in light of the uncertainty in the (as yet, not demonstrated) performance of key PTES components, namely the reciprocating-piston compressors and expanders. At the same time, PTES was also found to have a higher power capital cost, which makes its deployment less economically attractive for implementation at lower volumes. The results indicate that the complexity of the decarbonization challenge makes it difficult to identify clearly a 'best' technology and suggest that the uptake of either technology can provide significant system-level benefits. Highlights: PTES has higher power and energy capital costs than LAES. The variation in the capital costs of PTES is higher than that of LAES. The whole-system value of PTES is slightly higher than LAES. The whole-system value of the technologies varies depending on deployment. Lower carbon targets increase the system value of energy storage.